Left Ventricular Assist Device Infections and the Potential Role for Dalbavancin: A Case Report. (4th September 2019) - Howard-Anderson, Jessica; Pouch, Stephanie M; Sexton, Mary Elizabeth; Mehta, Aneesh K; Smith, Andrew L; Lyon, George M; Friedman-Moraco, Rachel
Abstract: Left ventricular assist device infections (LVADIs) are common but challenging to treat, often requiring prolonged courses of intravenous antibiotics. Dalbavancin could have a role in treating patients with chronic LVADIs given its less frequent dosing requirements. Here, we illustrate a case in which dalbavancin was used as suppressive therapy for an LVADI for greater than 7 months.